PEMBUKTIAN DALAM PERSPEKTIF HUKUM LINGKUNGAN - Yusuf Eko Nahuddin (University of Merdeka Malang, 2016)
This writing aims to know how the evidence in the perspective of environmental law that contains several aspects of the law dimension both civic and criminal in the provisions of environmental law about the evidence is known or added to the provisions of other evidence, as regulated in Article 96 letter f Management and Protection Environmental Act Number 32 of 2009 which is explained that the other means of evidence, which includes; information uttered, transmitted, received, or stored electronically, magnetically, optically, and/or otherwise; and or evidence of data, recordings, or readable, viewable, and audible information that can be issued with and/or without the assistance of any means, whether contained on paper, any physical object other then paper, or electronically recorded. This is to provide an illustration that the evidence in the perspective of environmental law has experienced a significant development to calibrate the evidentiary process which is certainly different from the provisions in Article 184 of the Criminal Procedure Code (Criminal Procedure Code) in the hope that in the case of environmental law can be easier uncover environmental-related crimes by law enforcement officials.